THE SYNTHESIS AND STUDY OF THE LUMINESCENCE PROPERTIES OF SOLID SOLUTIONS (Y1-X-Y-ZYBXERYHOZ)3AL5O12 WITH LASER EXCITATION - Egor I. Pozdnyakov (Вестник Северо-Кавказского федерального университета, 2022)
Synthesized solid solutions of (Y1-x-y-zYbxEryHoz)3Al5O12, studied their luminescence characteristics, the dependence of the intensity of the Stokes IR luminescence band 0,96-1.1 microns and 144-1.68 microns, 1,83-2,15 microns, the concentration of ions, Yb3+, Er3+, Ho3+, when excited by laser radiation with a wavelength of 0,94 microns. The analysis of the obtained relationships and determined the optimal composition of the phosphor (Y0,85-xYb0,1Er0,05Hox)3Al5O12, for maximum energy conversion efficiency from the near-infrared region at 2100 nm.